The next best thing [large type] : a novel - Weiner, Jennifer (Center Point Publishing, 2012)
Believing she is realizing her dreams when her sitcom is bought, television writer Ruth Saunders finds her happiness threatened by demanding actors and executives as well as an unrequited crush on her boss and her septuagenarian grandmother's upcoming wedding.